Establishing a model of peer support for pregnant persons with a substance use disorder as an innovative approach for engaging participants in the healthy brain and child development study - Florence Hilliard; Holly Horan; Aleksandra E. Zgierska; Renee C. Edwards (Developmental Cognitive Neuroscience)
The HEALthy Brain and Child Development (HBCD) Study, a multi-site prospective longitudinal cohort study, will examine human brain, cognitive, behavioral, social, and emotional development beginning prenatally and planned through early childhood. The goal is to recruit over 7000 caregiver-child dyads across the United States, with 25 % of the study population comprising children exposed in utero to substances to better understanding the effects of prenatal substance exposure on fetal and child development. However, barriers of mistrust for pregnant persons who are substance involved can create challenges to recruiting and retaining this population. The HBCD Study is utilizing a novel approach in research, the inclusion of support professionals (i.e. study navigators) as research team members to boost recruitment, engagement, and retention in this population and other marginalized and underrepresented groups. This article describes the conceptualization and early implementation of a support model utilizing certified peer support specialists, and the evolution to a broader study navigator model (SNM). Core skills, training, and support necessary for integrating such support professionals onto the research team are outlined. A reflection on challenges and next steps describes how the early implementation of the SNM encourages a paradigm shift in longitudinal research that humanizes and centers the participants.